2007
DOI: 10.3892/or.17.3.637
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of genetic polymorphisms in thymidylate synthase, uridine diphosphate glucoronosyltransferase and X-ray cross complementing factor 1 genes as a prognostic factor in advanced colorectal cancer patients treated with 5-fluorouracil plus oxaliplatin or irinotecan

Abstract: The aim of this study was to investigate the influence of combining thymidylate synthase (TS), X-ray cross complementing factor 1 (XRCC1) and uridine diphosphate glucoronosyltransferase (UGT1A1 * 28) polymorphism genotypes in response rate and time to progression (TTP) in metastatic colorectal cancer patients treated with 5-fluorouracil (5-FU) plus irinotecan or oxaliplatin (OXA). PCR, RFLP, allelic discrimination and direct sequencing were performed to elucidate TS, XRCC1 and UGT1A1 * 28 genotypes in blood fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
(26 reference statements)
0
14
0
1
Order By: Relevance
“…Other genetic variants in DNA repair genes have been associated with the outcome to oxaliplatin treatment. Among them, an SNP resulting in an amino acid change (Arg to Gln) in X-ray repair cross-complementing protein 1 (XRCC1) has been shown to correlate with a worse outcome in some tumors (49,(56)(57)(58). The XPD Lys751Gln polymorphism has also been found to be associated with the outcome after oxaliplatin treatment in colorectal and gastric cancer.…”
Section: The Glutathione Systemmentioning
confidence: 99%
“…Other genetic variants in DNA repair genes have been associated with the outcome to oxaliplatin treatment. Among them, an SNP resulting in an amino acid change (Arg to Gln) in X-ray repair cross-complementing protein 1 (XRCC1) has been shown to correlate with a worse outcome in some tumors (49,(56)(57)(58). The XPD Lys751Gln polymorphism has also been found to be associated with the outcome after oxaliplatin treatment in colorectal and gastric cancer.…”
Section: The Glutathione Systemmentioning
confidence: 99%
“…Therefore, the TS functional polymorphisms are under investigation for the possibility of optimising chemotherapy (Yong and Innocenti, 2007). Studies in patients with metastatic colorectal cancer showed that carriers of the TS 5 0 -UTR 3R (3G) and/or the TS 3 0 -UTR 6 þ alleles had adverse clinical outcomes (Pullarkat et al, 2001;Etienne et al, 2002;Park et al, 2002;Marcuello et al, 2004;Stoehlmacher et al, 2004;Martinez-Balibrea et al, 2007); however, such an association was not always detected (Lecomte et al, 2004;Jakobsen et al, 2005;Ruzzo et al, 2007a, b). Heterogeneity in clinical experimental conditions (Sorbye et al, 2007), in tumour burden (Köhne et al, 2002) and in genetic/molecular features in the presence of a multisite metastatic disease (Yokota, 2000) may explain variable results in these pharmacogenetic studies.…”
mentioning
confidence: 99%
“…It was discovered that the 3R3R genotype was related with poor outcomes for colorectal cancer patients treated with 5-FU3233. For GC patients receiving 5-FU regimens, Ott et al also found that 3R3R was a risk factor for the survival34.…”
Section: Discussionmentioning
confidence: 99%